The Beneficial Effects of Applied Physiology Study Guides on Dentistry Students' Learning - Rana Keyhanmanesh; Fariba Mirzaei Bavil; Morteza Ghojazadeh; Hadi Ebrahimi; Hossein Mazouchian; Mohammad Ali Ebrahimi Saadatlou (Tabriz University of Medical Sciences, 2014)
Introduction: Previous studies have shown that study guides are effective tools that recognize students' educational needs and help teachers to attain satisfactory results. Unfortunately, this effective learning tool has not been used in the coursework and teaching of basic sciences in Tabriz University of Medical Sciences. Therefore, this study was proposed to evaluate the effects of a study guide in an applied physiology course on the overall learning quality of dental students.Methods: In this semi-quasi experimental study, 45 dental and 63 medical students in an Applied Physiology course were included. A study guide was given to the dental students at the beginning of the course. At the end of the course, a final examination was held for both groups separately using the OSCE method. The medical and dental students' final scores were compared using a T-test with SPSS v.16 software. A 34-question Likert-scaled questionnaire was prepared by researchers to evaluate the experimental group's opinion about the effects of the study guide on their learning.Results: The final exam score of the dental students was 18.01±1.57, and it was 17.94±1.42 for the medical students. The final score of both groups was not different significantly (p=0.804). Based upon the questionnaire, the dental students believed that study guide significantly improved their knowledge and skills in applied physiology (Mean= 61.12±13.7). Conclusion: Use of a study guide improves both the attitude and knowledge of dental students in the applied physiology course.